1994
DOI: 10.1002/rcm.1290080706
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of explosives compounds using laser ionization time‐of‐flight techniques

Abstract: Resonance-enhanced multiphoton ionization has been used to detect the presence of vapour-phase explosive-type samples in a linear time-of-flight (TOF) mass spectrometer. In particular, nitrobenzene, 2-nitrotoluene, 2,4-dinitrotoluene, 2,4,64rinitrotoluene, ethylene glycol dinitrate, pentaerythritol tetranitrate (PETN), 1,3,5-trinitro-l,3,5-triazacyclohexane (RDX) and SEMTEX (PETN plus RDX plus plasticizer) have been analysed at a laser wavelength of 226.3 nm corresponding to a strong resonant transition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
(2 reference statements)
0
12
0
Order By: Relevance
“…LIMS has been employed to study energetic materials in the gas phase using nanosecond laser pulses . This method allows the rapid screening of many samples without the need for complicated preparation techniques such as are required in gas chromatography/mass spectrometry (GC/MS).…”
mentioning
confidence: 99%
“…LIMS has been employed to study energetic materials in the gas phase using nanosecond laser pulses . This method allows the rapid screening of many samples without the need for complicated preparation techniques such as are required in gas chromatography/mass spectrometry (GC/MS).…”
mentioning
confidence: 99%
“…Their studies focused on an understanding of the mass spectra obtained using ultrafast laser pulses in conjunction with time-of-flight mass spectrometry, M ϩ ion formation, and specific molecular fragments that could be assigned to a particular precursor species. Of particular interest was the demonstration of isomer dependent mass spectra for the three isomers of nitrotoluene.The motivation to apply femtosecond laser ionization to the study of explosives and ERCs originated from previous laser ionization work, which found that nanosecond laser ionization in the ultraviolet led to extensive molecular fragmentation [31][32][33][34][35][36]. The extensive fragmentation was determined to be non-useful for species-specific identification, even though abundant NO ϩ ions were observed in the mass spectra [37].…”
mentioning
confidence: 99%
“…The motivation to apply femtosecond laser ionization to the study of explosives and ERCs originated from previous laser ionization work, which found that nanosecond laser ionization in the ultraviolet led to extensive molecular fragmentation [31][32][33][34][35][36]. The extensive fragmentation was determined to be non-useful for species-specific identification, even though abundant NO ϩ ions were observed in the mass spectra [37].…”
mentioning
confidence: 99%
“…Laser ionization-TOF-techniques have been introduced to ionize explosive species (Marshall et al, 1994); femtosecond laser TOF has been used to analyze TNT and other nitro-aromatic molecules (Ledingham et al, 1995;Kosmidis et al, 1997). Recent studies have demonstrated the ability of ultrafast laser ionization to generate analyte molecular and structure-specific ions from nitro-aromatic compounds.…”
Section: Other Ionization Techniquesmentioning
confidence: 99%